A new species of the genus Penicillium isolated from the soil of the Chaco dry forest in Argentina - Silvestro, Luciana Belén (2025)
Abstract: Studies related to the diversity of species of genus Penicillium present in Argentina soils focus on evaluating the functionality and importance of fungi in ecosystems, but little attention has been focused on the search for new species. The Chaco dry forest in Argentina is a semiarid region belonging to the subregion of Neotropical dry forests, characterized by the presence of the plant of the genus Schinopsis Engl. Penicillium is a genus that belongs to the phylum Ascomycota, species of this are ubiquitous and present in a wide range of environmental conditions. The aim of this work is to describe a new species of Penicillium, Penicillium schinopsum sp. nov. This species separates phylogenetically into a new clade that made identification to the species level feasible and allowsthe assignment to a possible new section and series. The strain is a novel species of genus Penicillium ser. and sect. Schinopsiorum sect. nov., we propose the name Penicillium schinopsum sp. nov. This new proposal could be part of the subgenus Aspergilloides and it is phylogenetically related to sections Aspergilloides, Sclerotiorum, Charlesia, and Eremophila. The morphology and growth of the colony support phylogenetic separation. The main morphological characteristic that it showed was the fast growth rates of the colonies on all culture media tested except on CYA at 37 ºC, the green colour of the colony, the monoverticillate conidiophore with a long stipe, smooth-walled globose conidia and absence of sclerotia. We considered it necessary to continue advancing in the characterization to assess its biotechnological potential.